2004
DOI: 10.1046/j.0105-6263.2003.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric application of resazurin reduction assay to evaluate boar semen quality

Abstract: The resazurin reduction assay depends on the ability of metabolically active cells to reduce the resazurin redox dye to resorufin. In the present study we applied and made a diagnostic evaluation of a spectrophotometric application of the resazurin reduction assay to assess the colour change of resazurin reduction in butanol extracted colour to evaluate boar semen quality. Forty-one samples of boar semen from various breeds were included in the study. The absorption peaks for resazurin and resorufin were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…The resazurin test has been used since the 1950s to assess bacterial or yeast contamination in biological fluids (Erb and Ehlers 1950). It is also used to measure the semen quality (Wang et al 1998;Zrimsek et al 2004), corneal viability (Perrot et al 2003), mitochondrial function (Zhang et al 2004), quantity/proliferation of living organism (Mann and Markham 1998;Guerin et al 2001;Gabrielson et al 2002;Palomino et al 2002;Martin et al 2003), and different types of cells for its cytotoxicity, toxicology, and apoptosis (O'Brien et al 2000;Evans et al 2001;Putnam et al 2002;Batchelor and Zhou, 2004;Benavides et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The resazurin test has been used since the 1950s to assess bacterial or yeast contamination in biological fluids (Erb and Ehlers 1950). It is also used to measure the semen quality (Wang et al 1998;Zrimsek et al 2004), corneal viability (Perrot et al 2003), mitochondrial function (Zhang et al 2004), quantity/proliferation of living organism (Mann and Markham 1998;Guerin et al 2001;Gabrielson et al 2002;Palomino et al 2002;Martin et al 2003), and different types of cells for its cytotoxicity, toxicology, and apoptosis (O'Brien et al 2000;Evans et al 2001;Putnam et al 2002;Batchelor and Zhou, 2004;Benavides et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In M. tuberculosis, resazurin has been used successfully to test the susceptibility of active and dormant bacilli to anti-tuberculosis drugs by the resazurin microtiter assay (REMA) plate (6, 10, 13). Reduction of resazurin can be measured using a spectrophotometer due to its change in colour from blue (oxidized form) to pink (reduced form) (18). …”
mentioning
confidence: 99%
“…Studies have shown that there were positive relationships between ATP measurements and the percentage of spermatozoa with functional mitochondria following preservation of boar and canine semen (Fraser et al 2007, Dziekońska et al 2009, Kordan et al 2010). These methods can be complemented with the spectrophotometric application of the resazurin reduction test (RRT) to evaluate sperm quality (Zrimšek et al 2004). The RRT is based on the ability of metabolically active sperm cells to reduce the resazurin redox dye to resorufin, and was correlated with sperm characteristics, such as motility and viability (Dart et al 1994, Zrimšek et al 2004).…”
Section: Mitochondrial Functional Efficiencymentioning
confidence: 99%
“…These methods can be complemented with the spectrophotometric application of the resazurin reduction test (RRT) to evaluate sperm quality (Zrimšek et al 2004). The RRT is based on the ability of metabolically active sperm cells to reduce the resazurin redox dye to resorufin, and was correlated with sperm characteristics, such as motility and viability (Dart et al 1994, Zrimšek et al 2004). …”
Section: Mitochondrial Functional Efficiencymentioning
confidence: 99%